PsRPs26, a 40S Ribosomal Protein Subunit, Regulates the Growth and Pathogenicity of Puccinia striiformis f. sp. Tritici - Wang, Bing; Song, Na; Tang, Chunlei; Ma, Jinbiao; Wang, Ning; Sun, Yanfei; Kang, Zhensheng (Frontiers in Microbiology, 2019)
Eukaryotic ribosomes are essential for proliferation, differentiation, and cell growth. RPs26 is a ribosomal subunit structural protein involved in the growth and development process. Little is known about the function of PsRPs26 in pathogenic fungi. In this study, we isolated the RPs26 gene, PsRPs26, from Puccinia striiformis f. sp. tritici (Pst). PsRPs26 contains a eukaryotic-specific Y62–K70 motif and is more than 90% identical with its ortholog gene in other fungi. PsRPs26 was found to be localized in both the nucleus and cytoplasm. Expression of PsRPs26 increased when wheat seedlings were inoculated with the Pst CYR31 isolate. Moreover, knockdown of PsRPs26 by a host-induced gene silencing system inhibited growth and limited urediospore production in Pst. Our discovery that PsRPs26 may contribute to the pathogenicity of Pst and open a new way in the pathogenic function of PsRPs26 in cereal rust fungi.